Introduction - Felder, Ekkehard; Jacob, Katharina; Schwinn, Horst; Busse, Beatrix; Große, Sybille; Gvozdanović, Jadranka; Lobin, Henning; Radtke, Edgar (Handbuch europäische Sprachkritik online, 2018)
The "Online Handbook of Language Criticism - A European Perspective" offers a contrastive perspective of language criticism in European language cultures. The handbook is a periodic and multilingual online publication. Encyclopedic articles are published successively on selected topics that highlight key concepts in language criticism and that are of cultural relevance to the European perspective. The aim is thus to present a history of concepts of European language criticism. On the one hand, the handbook gives specific insights into the individual language cultures. On the other hand, it aims at comparing and contrasting them.